1984
DOI: 10.1007/bf00135168
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma cells growing in aggregates on a non-adhesive poly(HEMA) substrate exhibit polykaryocytosis but do not develop an increased metastatic capability

Abstract: B16-F1 melanoma cells were plated onto plastic tissue-culture dishes rendered non-adhesive for cells by coating with 0.12 per cent poly(2-hydroxyethyl methylacrylate), poly(HEMA). These growth conditions caused the normally flat, adherent B16-F1 cells to grow as single cells in suspension. Within 24 hours, the rounded cells formed aggregates and grew at a slower rate than control cells grown at the same density on untreated plastic dishes. Microscopic observations provided evidence that polykaryocytosis was oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Examples include glycation 77 and enzyme-induced 78 stiffening of collagen matrices, improved mechanical properties of tissue-engineered blood vessels by addition of retinoic and ascorbic acid, 79 as well as remodeling of collagen constructs by mechanical stresses. 80 In addition to the examples cited above, many other novel materials based on synthetic hydrogels such as polyethylene glycol, 81 polyacrylate derivatives, poly(2-hydroxyethyl methylacrylate), 82 and polyelectrolyte multilayers 83,84 are being designed for use in many different cellular systems. The synthetic hydrogels can be made alone or in combination with natural biopolymers such as polysaccharides, glycosaminoglycans, and protein polymers.…”
Section: Soft Materials In Biological Researchmentioning
confidence: 99%
“…Examples include glycation 77 and enzyme-induced 78 stiffening of collagen matrices, improved mechanical properties of tissue-engineered blood vessels by addition of retinoic and ascorbic acid, 79 as well as remodeling of collagen constructs by mechanical stresses. 80 In addition to the examples cited above, many other novel materials based on synthetic hydrogels such as polyethylene glycol, 81 polyacrylate derivatives, poly(2-hydroxyethyl methylacrylate), 82 and polyelectrolyte multilayers 83,84 are being designed for use in many different cellular systems. The synthetic hydrogels can be made alone or in combination with natural biopolymers such as polysaccharides, glycosaminoglycans, and protein polymers.…”
Section: Soft Materials In Biological Researchmentioning
confidence: 99%
“…B16 cells grown in a rounded state on polyhema substrates have been reported to exhibit a greater lung-colonizing ability than their tissue culture plastic-grown counterparts [55]. More recently, this finding has been questioned [56]. Nonetheless, we postulated that such rounded cells might exhibit increased degradative activity, since it has been reported that collagenase activity of similarly rounded synovial cells is increased over that of their "flat" counterparts [57].…”
Section: Discussionmentioning
confidence: 89%
“…The stable cell line HEK293/pKIA was established by screening the transfected cells with 300 ug/mL Geneticin (ThermoFisher). For cell culture in suspension, the culture plates were coated with poly-HEMA as described before [ 71 ].…”
Section: Methodsmentioning
confidence: 99%